Life-threatening antineutrophil cytoplasmic antibody–associated vasculitis after influenza A H1N1 infection requiring veno-venous extracorporeal membrane oxygenation. (September 2020) - Frantzeskaki, Frantzeska G.; Dimopoulos, Stavros; Konstantonis, Dimitrios; Katsibri, Pelagia; Kostopanagiotou, Kostantinos; Theodorakopoulou, Maria; Diakaki, Chrysi; Dougenis, Dimitrios; Boumpas, Dimitrios; Karabinis, Andreas; Armaganidis, Apostolos; Tsangaris, Iraklis
Introduction: Antineutrophil cytoplasmic autoantibody–associated vasculitis is an immune-mediated necrotizing vasculitis, affecting small- and medium-sized vessels. Case report: A 22-year-old female patient with free medical history presented with life-threatening pulmonary hemorrhage due to antineutrophil cytoplasmic autoantibody–associated vasculitis, temporarily associated with influenza A H1N1 infection. Due to rapidly worsening respiratory failure, despite conventional management, veno-venous peripheral extracorporeal membrane oxygenation was initiated and continued for 26 days, with subsequent renal replacement therapy. Discussion: We present a case of severe antineutrophil cytoplasmic autoantibody–associated pulmonary vasculitis, managed with veno-venous extracorporeal membrane oxygenation at the initial phase. Despite the significant challenges raised with the use of extracorporeal membrane oxygenation in pulmonary hemorrhage cases, extracorporeal membrane oxygenation may have a significant impact on outcome in this setting, by providing adequate time for a successful immunosuppressive treatment.